Evaluating the Citations and Social Attention Difference Between Open Access and Paywalled LIS Literature - C, Vysakh; H, Rajendra Babu (DESIDOC Journal of Library & Information Technology, 2023)
The purpose of the present study is to assess the open access advantages in getting citations and social media attention for Library and Information Science (LIS) literature indexed in the dimensions database and tracked by Altmetric Explorer. An advanced search in the Altmetric Explorer was carried out to collect the needed data for the study and subjected to parametric and non-parametric tests to achieve the objectives. The results discovered differences in citations and altmetric attention benefits between Open Access (OA) and pay-walled LIS literature. Open access was found to have more citations and altmetrics than Non-Open Access (NOA). Furthermore, green OA outputs were reported to have more citations among the OA categories, while hybrid OA attracted more social media attention. The results of the present study offer insights for authors in deciding where to publish in order to maximise the scientific and social impact of their writings.